Effects of dietary Clostridium butyricum and fructooligosaccharides, alone or in combination, on performance, egg quality, amino acid digestibility, jejunal morphology, immune function, and antioxidant capacity of laying hens - Obianwuna, Uchechukwu Edna; Qiu, Kai; Wang, Jing; Zhang, Hai-jun; Qi, Guang-hai; Huang, Ling-ling; Wu, Shu-geng (Frontiers in Microbiology, 2023)
The present study was conducted to evaluate the effects of Clostridium butyricum (CB) and fructooligosaccharide (FOS) singly or combined, on performance, egg quality, amino acid digestibility, jejunal morphology, immune function and antioxidant capacity in peak-phase laying hens. A total of 288 Hy-Line Brown laying hens (30 weeks of age) were randomly assigned to 4 dietary groups that included basal diet, basal diet + 0.02 % of C. butyricum (zlc-17: 1×109 CFU/g) (PRO), basal diet + 0.6% fructooligosaccharide (FOS) (PRE), and basal diet + 0.02% C. butyricum + 0.6% fructooligosaccharide (SYN) for 12 weeks. Each treatment had 6 replicates with 12 birds each. The results demonstrated that probiotics (PRO), prebiotics (PRE) and synbiotics (SYN) (P ≤ 0.05), respectively, exerted a positive effect on the performance and physiological response of the birds. There were significant increases in egg production rate, egg weight, egg mass, daily feed intake and reduced number of damaged eggs. and zero mortality rate due to dietary PRO, PRE and SYN (P ≤ 0.05) respectively. Also, feed conversion was improved by PRO (P ≤ 0.05). In addition, egg quality assessment showed that; eggshell quality was increased by PRO (P ≤ 0.05) and albumen indices (Haugh unit, thick albumen content, and albumen height) were enhanced by PRO, PRE and SYN (P ≤ 0.05). Further analysis showed that PRO, PRE and SYN (P ≤ 0.05), reduced heterophil to lymphocyte ratio, increased antioxidant enzymes and immunoglobulin concentration. Although spleen index was higher for PRO (P ≤ 0.05) group. The significant increase in villi height, villi width, villi height to crypt depth ratio and reduced crypt depth were obvious for PRO, PRE and SYN (P ≤ 0.05). Furthermore, improved nutrient absorption and retention evidenced by increased digestibility of crude protein and amino acids, were notable for PRO, PRE and SYN (P ≤ 0.05) group. Collectively, our findings revealed that dietary CB and FOS alone, or combined, enhanced productive performance, egg quality, amino acid digestibility, jejunal morphology and physiological response in peak-phase laying hens. Our results would provide direction on nutritional strategies for gut enhancers and better physiological response of peak laying hens.